Inquiry-based Augmented Reality Activities for Enhancing Reading Comprehension and Engagement of EFL Secondary School Students - Marwa Rehab; ahmed aliweh (International Journal of Advanced Humanities Research)
The present study investigated the effectiveness of using Inquiry based augmented reality activities for enhancing reading comprehension and engagement among first year secondary school students. For this purpose, sixty-six secondary school students were assigned to an experimental and control group, 33 students each. During the implementation, the participants were engaged in various inquiry based augmented reality activities. Pre and post-tests of reading comprehension skills and an engagement scale were administered to examine the effectiveness of these activities on students' reading comprehension and engagement. Results revealed that Inquiry based augmented reality activities had a significant effect on students' reading comprehension and engagementThe present study investigated the effectiveness of using Inquiry based augmented reality activities for enhancing reading comprehension and engagement among first year secondary school students. For this purpose, sixty-six secondary school students were assigned to an experimental and control group, 33 students each. During the implementation, the participants were engaged in various inquiry based augmented reality activities. Pre and post-tests of reading comprehension skills and an engagement scale were administered to examine the effectiveness of these activities on students' reading comprehension and engagement. Results revealed that Inquiry based augmented reality activities had a significant effect on students' reading comprehension and engagement